2013
DOI: 10.4049/jimmunol.1201881
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Cooperates with G-CSF To Induce Protumor Function of Neutrophils in Bone Marrow by Enhancing STAT3 Activation

Abstract: Neutrophils are known to have antitumor potential. However, in recent years the tumor-promoting effect of neutrophils has been well demonstrated. So far, it remains unclear what causes the conversion of neutrophil function from tumor suppressive to tumor promoting. In this article, we report that the conversion of murine neutrophil function occurs in bone marrow, and that IL-6 cooperation with G-CSF is required for this conversion. IL-6 cooperated with G-CSF to modulate neutrophils in bone marrow, altering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
113
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 49 publications
8
113
0
1
Order By: Relevance
“…The actions of G-CSF may therefore require the interaction with other cytokines and growth factors in vivo . For example G-CSF is known to cooperate with stem cell factor in haematopoiesis (Duarte and Franf, 2002) and IL-6 during bone marrow stem cell tumour progression (Yan et al, 2013). Alternatively, it may act directly on other cell populations, such as immune cells to stimulate the release of factors that are able to act directly on muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…The actions of G-CSF may therefore require the interaction with other cytokines and growth factors in vivo . For example G-CSF is known to cooperate with stem cell factor in haematopoiesis (Duarte and Franf, 2002) and IL-6 during bone marrow stem cell tumour progression (Yan et al, 2013). Alternatively, it may act directly on other cell populations, such as immune cells to stimulate the release of factors that are able to act directly on muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…In breast and lung carcinoma models, exogenous or tumor-derived G-CSF promotes expansion of myeloid-derived suppressor cell (MDSC) subsets within the circulation and tumor microenvironment (19, 32). These MDSCs in turn secrete pro-angiogenic factors and down-regulate pro-apoptotic TRAIL and MPO leading to tumor progression and metastatic spread to the lung (33, 34). These results are consistent with our findings that G-CSF promotes overall tumorigenicity and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is however interesting that we observed the presence of both IL6 and G-CSF in TCM because previous work by others have shown that IL6 and G-CSF are produced by tumor and/or stromal cells in malignant tumors (Shojaei et al, 2007). IL6 and G-CSF in conjunction with phospho-STAT3 have been implicated in the protumor function of neutrophils (Yan et al, 2013). Furthermore, G-CSF is involved in promoting tumor angiogenesis (Okazaki et al, 2006; Shojaei et al, 2009) and increased levels of serum IL-6 have been associated with poor prognosis in human mammary cancer (Zhang and Adachi, 1999).…”
Section: Discussionmentioning
confidence: 99%